Arbetsterapeutiska interventioner för kvinnor med stress-relaterad ohälsa : En litteraturöversikt - Forss, Hanna; Landerstedt, Tove (2013)
The purpose of this literature review was to identify the research front and compile occupational therapy interventions and women's experiences of stress-related disorder in working age. The collection of data was made through a systematic literature search in databases via Luleå University libraries and secondary searches. The articles were reviewed for quality and value as evidence. The result consisted of ten qualitative and quantitative research articles. The articles were analyzed and presented by an occupational therapy theoretical model to clarify how interventions and experiences affect human activity and occupational performance by volition, habituation, performance capacity, and the environment. The results were presented in three parts: occupational therapy interventions, the interventions' effect/change, value as evidence and the experience of women in daily occupations. The occupational therapy intervention for women with stress-related disorder affects the volition, habituation, performance capacity and the environment. The interventions had a positive effect on including returning to work, the pursuit of meaningfull occupations and quality of life. The women's experience in activities of daily living with stress-related disorder is mainly aimed to volition, habituation and the environment. The result of the literature review contributes to occupational therapists use of interventions for women with stress-related disorder that has a positive effect/change. It also contributes to an increased understanding of rehabilitation and useful strategies of the client group from the experience. However, the interventions need to be clarified and more research is needed in the area of women with stress-related disorder, particularly quantitative intervention studies to strengthen the grade of evidence. The research is ongoing which indicates that stress-related illness is a current area for occupational therapists. Validerat; 20130612 (global_studentproject_submitter)